Quandaries and Queries


I am a grade 9 student and i do not understand a question. Plz help!
OK here it is........ (2x+5y-6) + (3x-4y+12)
Thank You


Hi GG,

You didn't give us any instructions but I expect you are to simplify this expression. Since the signs preceeding the parentheses is positive (there is an implicit + before the first parenthesis) you can remove the parentheses and get

2x + 5y - 6 + 3x - 4y + 12

At this point you should collect like terms, that is callect all the "x-terms", all the "y-terms" and all the constant terms. I get

2x + 3x + 5y - 4y - 6 + 12

Looking at this expression you have two x's and 3 x's which is five x's. That is

2x + 3x = 5x

you have five y's and minus four y's which is one y since 5-4=1. That is

5y - 4y = 1y = y

Finally -6+12=6 so you get

(2x+5y-6) + (3x-4y+12) = 2x + 3x + 5y - 4y - 6 + 12 = 5x + y + 6



Go to Math Central